A test of the fast–slow plant economy hypothesis in a subtropical rain forest. (2nd November 2021) - Rodrigues, Arthur V.; Pastório, Fábio F.; Bones, Fábio L. V.; Esquivel-Muelbert, Adriane; Vibrans, Alexander C.; de Gasper, André L.
ABSTRACT: Background: The fast–slow plant economy hypothesis predicts strong co-variation in key resource-use traits due to the trade-off between growth and survival of species. Accordingly, it is expected that trait variation may be reduced to a single dimension along a growth-survival gradient. However, some studies warn against such reductionism and promote investigating how a multi-dimensional trait space can be interpreted in a growth-survival trade-off context. Aim: To quantify the dimensionality of the trait variation of trees and tree-like species to test the fast–slow plant economy hypothesis in a subtropical rain forest. Methods: We conducted phylogenetic Principal Components Analyses and correlation test on traits describing carbon and water economy in the leaves, stem, and seeds to evaluate the dimensionality of trait space and covariation among traits. Results: We found five axes explaining 71% of trait variation. The first and second axes described carbon capture and allocation. Water use economy was related to carbon capture and was also represented on the third axis. Stomata traits were related to the fourth axis and plant potential height to the fourth and fifth axes. Conclusion: The high dimensionality we found suggests that ecological strategies to water and carbon use are diverse in (sub)tropical montane forest species. Therefore, contrary to the expectation, these plants could use different ecological strategies to achieve a similar fitness in the growth–survival gradient.